A coupled cohesive modeling approach for predicting fractures in low alloy steel under high-pressure hydrogen gas. (6th January 2021) - Cui, T.C.; Shang, J.; Hua, Z.L.; Peng, W.Z.; Shi, J.F.; Xu, P.; Gu, C.H.
Abstract: Hydrogen-induced fractures usually occur in low alloy steel under the influences of stress concentration and high-pressure hydrogen gas. The purpose of this study was to predict the hydrogen-induced fracture behavior of low alloy steel under a high-pressure hydrogen gas environment. The hydrogen-sensitive cohesive model was used for the prediction of crack propagation, which took into account the influence of high-pressure hydrogen gas. The coupling model between hydrogen diffusion and plastic deformation was also applied by using UMAT and UMATHT subroutines. Disk pressure tests were performed on 4130X steel with different hydrogen pressure rise rates to demonstrate the coupled cohesive modeling approach. The hydrogen-induced fracture behaviors of the 4130X steel disk predicted by the proposed approach showed good agreement with experimental results. Numerical results indicated that hydrogen accumulated at the anchorage of the disk and reduced the maximum cohesive stress with the enhancement of localized plastic deformation. Therefore, the crack growth rate of the disk increased under a high-pressure hydrogen gas environment with relatively low maximum cohesive stress and low fracture energy. Graphical abstract: Image 1 Highlights: A method for predicting hydrogen induced fracture in low alloy steel is proposed. The cohesive model are affected by hydrogen pressure and hydrogen concentration. Disk pressure tests are performed on the 4130X steel to demonstrate the approach. The predicted fracture behaviors show good agreement with experimental results. The low σmax and the low G IC accelerate the crack propagation of the 4130X disk.